Cost effectiveness of crack treatment methods: A field study - Mithil Mazumder; Hyun Hwan Kim; Soon-Jae Lee; Moon-Sup Lee (Journal of Traffic and Transportation Engineering (English ed. Online), 2019)
In the United States, more than 94% highways are paved with asphalt materials and placing crack sealant materials has been a common pavement maintenance for decades. Crack sealing treatment includes the use of a router to create a reservoir on the intended cracks whereas crack filling is given without doing any modification to the crack wall. Although the initial cost of crack sealing is higher, it is expected to have a longer service period compared to crack filling. There is little research on comparison of short and long term cost effectiveness between these two treatments using the real field cost data analysis. In this study four test sites in Texas were treated with crack filling and sealing using the same sealant material and finishing technique. Cost effectiveness of both treatments was measured in terms of initial, annual average and life cycle cost based on the cost inputs during construction. In general, the results of this study indicated that (1) on an average approximately 45% initial cost increase was estimated with the two routing configurations of crack sealing; (2) material and labor cost is found to have the most significant effect on the higher initial cost of crack sealing compared to other associated costs; (3) annual average and life cycle costs have shown that crack sealing is more cost effective pavement maintenance compared to crack filling over a long period of time; (4) agency cost is observed to be reduced by approximately 24% with crack sealing treatment based on the 35 year analysis period. Keywords: Crack sealing, Crack filling, Initial cost, Annual average cost, Life cycle cost